Improving network performance by enabling explicit congestion notification (ECN) in SCTP control chunks - Mohamad Tahir, Hatim; Md Said, Abas; Elhalabi, Mohammed J. M.; Puteh, Nurnasran; Othman, Azliza; Muhd Zain, Nurzaid; Md Dahalin, Zulkhairi; Ismail, Muhammad Hafiz; Mohd Zaini, Khuzairi; Hussin, Mohd Zabidin (Springer Berlin Heidelberg, 2011)
The need for a reliable transmission protocol that can cover the Transport Control Protocol (TCP) and User Datagram Protocol (UDP) has prompted the Internet Engineering Task Force (IETF) to define a new protocol called the Stream Control Transmission Protocol (SCTP).This paper proposes adding Explicit Congestion Notification (ECN) mechanism into SCTP chunks (INIT chunk, and INIT-ACK chunk) to reduce the delay of transferring important data during congestion as compared with the TCP and UDP protocols.This paper also discusses the details of adding ECN, and the reason for choosing Random Early Detection (RED). Through the experimental analysis, we compare SCTP enabled ECN in INIT-ACK chunk to SCTP without ECN enabled in INIT-ACK chunk and demonstrate the result of ECN impact on SCTP delay time.